Salvianolic acid A alleviates cardiovascular injury in rats with chronic kidney disease by activating the PI3K/Akt/Nrf2/HO-1 and SIRT1/TLR4/NF-κB/P38 signaling pathways - Chengkai Wu; Bosai He; Xiao Wang; Yang Zou; Ruixin Ma; Yanting Gu; Jian Huang; Songping Li; Jinhui Wang; Jiahong Wang (Journal of Functional Foods, 2023)
Salvianolic acid A (Sal A), extracted from Danshen, has proven efficacy in preventing cardiovascular diseases. However, its effect on mitigating vascular damage caused by chronic kidney disease remains unclear. This study investigated the therapeutic effects and underlying mechanisms of Sal A in a rat model of 5/6 Nephrectomized (5/6Nx). The results of our study showed that Sal A effectively reduced the levels of kidney injury markers. Histopathological analysis revealed that Sal A dose-dependently attenuated arterial injury. The attenuation was characterized by the thinning of vascular endothelium and reduced endothelial cell hyperplasia, accompanied by decreased expression of OPN and C-Reaction Protein (CRP). Further investigations revealed that Sal A alleviated oxidative stress-induced vascular injury by activating the Phosphoinositide 3-kinase (PI3K)/Protein Kinase B(Akt)/Nuclear factor erythroid2-related factor 2(Nrf2)/Heme Oxygenase 1(HO-1) signaling pathway. Furthermore, Sal A inhibited inflammation by suppressing the Sirtuin-1(SIRT1)/Toll-like receptor 4(TLR4)/Nuclear factor kappa-B(NF-κB)/P38 signaling pathway and reducing the expression of pro-inflammatory cytokines. Our oxidative stress and inflammation cell models also supported these findings. In conclusion, Sal A treatment effectively attenuated vascular injury in 5/6Nx rats and exerted dual antioxidant and anti-inflammatory effects.